The role of culture and traditions in how young children's identities are constructed. Issue 1 (2nd January 2019) - Eaude, Tony
ABSTRACT: This article explores how cultures and traditions influence the construction of young children's identities. Identity is conceptualised as a constantly changing narrative based on how an individual sees him or herself and how s/he is perceived. We all have multiple, intersecting identities. Different meanings of culture are discussed, highlighting norms and values, 'culture-as-the-arts', and space for growth. Primary and secondary socialisation is emphasised, recognising the influence factors such as gender, race, class and religion. The effect of the home and of the macro-culture and different micro-cultures and traditions is considered. In relation to children's spirituality, trusting relationships and hospitable environments, and the need to counter messages given by an individualistic and consumerist macro-culture are highlighted. An apprenticeship approach is advocated, where adults encourage questioning and strive to maintain children's sense of agency, with a gradual transfer of power as children become older and/or more confident. It is suggested that researchers and practitioners should take more account of external factors such as gender, race and class in relation to children's spirituality.